HUBUNGAN STATUS GIZI IBU HAMIL DENGAN KEJADIAN INTRA UTERINE FETAL DEATH (IUFD ) DI RUANG VK RSUD. ABDUL WAHAB SYAHRANIE SAMARINDA TAHUN 2016 - fauziah fauziah fauziah (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2017)
Abstract Intrauterine Fetal Death (IUFD) is the death of the fetus while stil in the womb. The incidence of IUFD in the world approximately reaches the number of 2,14 – 3,82 million cases. From the national health statistic data, there are 7,6 million cases of perinatal death and 57% of that comes from IUFD. Around 98% of perinatal deaths happened in the developing countries which includes Indonesia. There are several factors which can contribute to IUFD, such as: maternal factor, fetal factor, and abnormality of umbilical cord factor (including placenta). IUFD can be prevented by correcting either lack of nutrition or excess nutrition in pregnant women regarding with the recommended daily allowance for pregnant women per day. This research’s aim is to study and explain the correlation of Pregnant Women Nutritional Status with the incidence of Intrauterine Fetal Death (IUFD) in maternity ward of Abdul Wahab Sjahranie Hospital in Samarinda 2016. The population is all 73 of pregnant women registered in Abdul Wahab Sjahranie Hospital in Samarinda in the month of January - April 2016 by using quota sampling method. Instrument used is the checklist. Data analysis was done by using univariat analysis of frequency distribution, bivariat by chi square. From 73 pregnant women (100%), there are 39,7% with Severe Nutritional Status who experienced IUFD and only 20,5% didn’t experience IUFD. From 60,3% pregnanti women with Good Nutritional Status, there are 11% who experienced IUFD while the rest 49,3% did not have IUFD. The result of chi square (x2) and Odd Ratio (OR), we got p vaue = 0,006 and OR (Odd Ratio) = 4,821 with deviance degree to population (ᾀ) of 5% (0,05). From this, we can conclude hat p value = 0,006 < ᾀ = 0,05. Thus, Ho is rejected which means that there is correlation between nutritional status of pregnant women with Intrauterine Fetal Death (IUFD). There is correlation between severe nutritional status of pregnant women with increasing incidence of IUFD as much as 5 times bigger than pregnant women with good nutritional status. For health care department to increase socialization, planned, organized and continuous. Information about the importance of nutrition in pregnant women to decrease the risk of IUFD incidence Key words: Nutritional Status, IUFD Abstrak Intra Uterine Fetal Death (IUFD) merupakan kematian janin. Angka insidensi kematian janin di dunia diperkirakan mencapai rentang 2,14 – 3,82 juta jiwa.Dari data pusat statistik kesehatan nasional diperkirakan 7,6 juta dari kematian perinatal 57% diantaranya merupakan IUFD. Sekitar 98% kematian perinatal terjadi di negara berkembang salah satunya Indonesia, ada beberapa faktor yang berhubungan dengan kejadian IUFD yaitu faktor ibu, faktor janin dan faktor kelainan tali pusat (termasuk plasenta). IUFD dapat dicegah salah satunya adalah status gizi ibu hamil yang tidak mencukupi atau bahkan melebihi dari jumlah gizi yang seharusnya dikonsumsi. Tujuan penelitian ini untuk mempelajari dan menjelaskan hubungan Status Gizi Ibu Hamil dengan Kejadian Intra Uterine Fetal Death (IUFD) di Ruang VK RSUD. Abdul Wahab Sjahranie Samarinda Tahun2016. Populasi penelitian adalah seluruh ibu hamil yang terdaftar di RSUD.Abdul Wahab Sjahranie tahun 2016pada bulan Januari – April 2016 sebanyak 73 orang menggunakan quota sampling. Instrument yang digunakan adalah checklist. Analisis data menggunakan analisis univariat distribusi frekuensi, bivariat dengan chi square. Hasil dari 73 orang (100%) ibu hamil dengan kategori Status Gizi Buruk 39,7%, yang mengalami IUFD sebanyak 20,5% dan yang tidak mengalami IUFD 19,2%. Kategori Status Gizi Baik 60,3%dengan IUFD 11% dan yang tidak IUFD 49,3%, hasil Chai Square (x2) dan Odd Ratio (OR) didapat P value = 0,006 dan Odd Ratio (OR) = 4,821 dengan derajat penyimpangan terhadap populasi (α) sebesar 5% (0,05), dapat disimpulkan bahwa P value = 0,006 < α = 0,05 maka Ho ditolak yang berarti ada hubungan antara status gizi ibu hamil dengan kejadian intra uterine fetal death (IUFD). Kesimpulan bahwa ibu hamil dengan status gizi buruk dapat mengalami IUFD 5 kali lebih besar dibandingkan ibu hamil dengan status gizi baik. Saran bagi instansi dan institusi kesehatan untuk meningkatkan sosialisasi, informasi yang terencana, terarah dan berkesinambungan tentang pentingnya gizi pada ibu hamil untuk menurunkan resiko kejadian IUFD. Kata Kunci : Status Gizi, IUFD